THE EFFECT OF BRAND AMBASADOR AND BRAND IMAGE ON BUYING INTEREST OF SCARLETT WHITENING WITH TRUST AS AN INTERVENING VARIABLE (Case Study of Scarlett Whitening Users in Kefamenanu City) - Bani, Marlinda Pala; Rado, Bernadus Ghawa; Taena, Emanuel Tati; Lake, Yeremias ,; Aksa, Adi Faisal; Seran, Rikhardus Bria; Natasi, Maria Magdalena Eno (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
The problems identified from this study are the lack of marketing strategies through advertising so that consumers lack product information which causes minimal purchases of Scarlett products, and the emergence of many new skincare brands with better quality makes competition even tighter, while making it difficult for the Scarlett Whitening Brand to become the most favorite brand. The purpose of this study was to determine the Brand Ambassador and Brand Image mediated by Trust on Purchase Interest of Scarlet Whitening Products. The method used in this study is an intervening variable using a statistical processing application. The results showed the t-statistic value of brand ambassadors on purchase interest of 13.024> t-table 1.96. the t-statistic value of brand ambassadors on purchase interest of 10.457> t-table 1.96. The t-statistic value of brand ambassadors on purchase interest is 12.030> t-table 1.96, the t-statistic value of brand ambassadors on purchase interest is 14.672> t-table 1.96, the t-statistic value of brand ambassadors on purchase interest is 14.801> t-table 1.96, the t-statistic value of brand ambassadors on purchase interest is 8.712> t-table 1.96, the t-statistic value of brand ambassadors on purchase interest is 9.483> t-table 1.96. So it can be said that Brand Ambassador and Brand Image on Purchase Interest with Trust as an intervening in the Kefamenanu City community have a positive influence.